2012
DOI: 10.1016/j.physleta.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Layer and size dependence of thermal conductivity in multilayer graphene nanoribbons

Abstract: Using non-equilibrium molecular dynamics method(NEMD), we have found that the thermal conductivity of multilayer graphene nanoribbons monotonously decreases with the increase of the number of layers, such behavior can be attributed to the phonon resonance effect of out-of-plane phonon modes. The reduction of thermal conductivity is found to be proportional to the layer size, which is caused by the increase of phonon resonance. Our results are in agreement with recent experiment on dimensional evolution of ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 45 publications
5
45
1
Order By: Relevance
“…The phonon energy spectra have been theoretically investigated using Perdew-Burke-Ernzerhof generalized gradient approximation (GGA) [38][39][40], valence-force-field (VFF) and Born-von Karman models of lattice vibrations [41][42][43][44][45][46], continuum approach [47][48][49], first-order local density approximation [39,50,51], fifth-and fourth-nearest neighbor force constant approaches [40,52] or utilized the Tersoff, Brenner or Lennard-Jones potentials [53][54][55]. The thermal conductivity investigations have been performed within molecular dynamics simulations [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], density functional theory [73,74], Green's function method [75,76] and Boltzmann-transport-equation (BTE) approach [31,[41][42][43]…”
Section: Theory Of the Thermal Conductivity Of Graphene And Gnrmentioning
confidence: 99%
See 1 more Smart Citation
“…The phonon energy spectra have been theoretically investigated using Perdew-Burke-Ernzerhof generalized gradient approximation (GGA) [38][39][40], valence-force-field (VFF) and Born-von Karman models of lattice vibrations [41][42][43][44][45][46], continuum approach [47][48][49], first-order local density approximation [39,50,51], fifth-and fourth-nearest neighbor force constant approaches [40,52] or utilized the Tersoff, Brenner or Lennard-Jones potentials [53][54][55]. The thermal conductivity investigations have been performed within molecular dynamics simulations [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], density functional theory [73,74], Green's function method [75,76] and Boltzmann-transport-equation (BTE) approach [31,[41][42][43]…”
Section: Theory Of the Thermal Conductivity Of Graphene And Gnrmentioning
confidence: 99%
“…Graphene and GNRs also demonstrated an intriguing dependence of the thermal conductivity on their geometrical parameters: lateral sizes and shapes [41][42][43]49,[68][69][70][71]85]. Using the BTE approach, Nika et al [43] have demonstrated that RT thermal conductivity of a rectangular graphene flake with 5 µm width increases with length L up to L ~ 40-200 µm and converges for L > 50-1000 µm in dependence on the phonon boundary scattering parameter p (see Figure 2a).…”
Section: Theory Of the Thermal Conductivity Of Graphene And Gnrmentioning
confidence: 99%
“…However, there is no universally accepted underlying mechanism for the size dependence of the thermal conductivity in graphene [127,132,[138][139][140][141]. In the out-of-plane direction, the thermal conductivity for graphene decreases with increasing layer number as there are more phononphonon scattering channels in thicker few-layer graphene [138,[142][143][144][145][146][147][148][149].…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…In case of narrower GNRs, the reduced edge-localized phonon effect is dominant with the increase of width leading to the increased thermal conductivity which is reflected in our study range. However, for a large enough width, more and more phonons will be activated with remarkably significant phonon's Umklapp effect and as a consequence, the thermal conductivity decreases with the increase of width of graphene nanoribbon [22,37,43]. Figure 9.…”
Section: Length Dependence Of Thermal Conductivitymentioning
confidence: 99%